Resolving agricultural disputes in Cuba - McCormack Bequer, Maritza de la Caridad; Cruz Legón, Mayra (Przegląd Prawa Rolnego, 2023)
The experience which the Ministry of Agriculture has gained regarding agricultural administrative proceedings shows that within the existing procedures there are still certain deficiencies in the regulation and the handling of cases. The aim of this article is to present them and justify the need for their modernisation in accordance with the regulations of the Cuban Magna Carta and the law of administrative proceedings. It is further claimed the current procedures do not ensure efficient solutions as the socially sensitive nature of agricultural issues requires particularly reliable and effective mechanisms that would also cause the least possible damage to those concerned and to the property in dispute. Therefore the reform should focus on the necessary modernisation of the current procedures and the development of a model that would ensure a greater speed of agricultural proceedings. This will also require the establishment of an agricultural chamber or designation of special purpose sections in People’s Courts.